Optimisation of pre-harvest sago frond sap for the production of l-lactic acid using Lactococcus lactis IO-1 - Muhammad Norhelmi, Ahmad; Dayang Salwani, Awang Adeni; Nurashikin, Suhaili; Kopli, Bujang (Elsevier, 2022)
The major restriction of sago palm plantation is the long maturation period for the starch extraction. As such, alternative commodity has to be identified to increase commercial value of sago palm especially from the by-product. Sago frond has been harvested to have numerous advantages as an alternative substrate for the production of biomaterial and biofuel such as lactic acid and bioethanol. This study focuses on effective approach to maximise the concentration of sugar in the substrate and to identify the ideal concentration of sago frond sap (SFSp) as sole media to produce l-lactic acid and grow L. lactis IO-1. Result shows that SFSp extracted from sago rachis using a roller press machine contained glucose (43.8 g/L), xylose (17.3 g/L) as free sugars and starch (5.55 g/L). Combination of enzymatic hydrolysis and sterilisation pre-treatment was found to maximise the concentration of total carbon source (68 g/L) and sterilised sago frond sap suitable to be used for fermentation process. The ideal con centration of SFSp that was determined at 50% dilution produces the highest amount of l-lactic acid (24.02 g/L) synergist by most efficient sugar consumption (89.93%). The use of SFSp as fermentation medium for l-lactic acid production generated maximum biomass concentration of 14.53 g/L. The utilisation of SFSp extracted from pre-harvest sago frond as substrate promote efficiency of l-lactic acid production associated to exceptional growth performance of L. lactis IO-1. In conclusion, the concept of utilizing byproduct from sago palm as novel raw material promise reliable resources and superiority of L. lactis IO-1 to metabolise sugar in SFSp promote lucrative and ethical production of l-lactic acid.